2020
DOI: 10.1038/s41419-020-2545-6
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomal miR-25-3p from mesenchymal stem cells alleviates myocardial infarction by targeting pro-apoptotic proteins and EZH2

Abstract: Mesenchymal stem cell (MSC) therapy is a promising approach against myocardial infarction (MI). Studies have demonstrated that MSCs can communicate with other cells by secreting exosomes. In the present study, we aimed to identify exosomal microRNAs that might contribute to MSC-mediated cardioprotective effects. Primary cardiomyocytes were deprived of oxygen and glucose to mimic MI in vitro. For the animal model of MI, the left anterior descending artery was ligated for 1 h, followed by reperfusion for 12 h. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 46 publications
0
72
0
Order By: Relevance
“…Similarly, Li Y. et al (2019) demonstrated that exosomal miR-301 derived from bone marrow MSCs (BMSCs) reduces the area of myocardial infarction and improves autophagy of myocardial cells. Further, Peng et al (2020) showed that miR-25-3p secreted by MSCs reduces myocardial infarction area by targeting EZH2; Wen et al (2020) showed that exosomal miR-144 derived from MSCs targets the regulation of the PTEN/AKT pathway, thus improving the apoptosis of cardiomyocytes under hypoxia. Geng et al (2020) showed that miR-143, which is derived from serum exosomes, promotes myocardial angiogenesis through the IGF-IR/NO pathway.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…Similarly, Li Y. et al (2019) demonstrated that exosomal miR-301 derived from bone marrow MSCs (BMSCs) reduces the area of myocardial infarction and improves autophagy of myocardial cells. Further, Peng et al (2020) showed that miR-25-3p secreted by MSCs reduces myocardial infarction area by targeting EZH2; Wen et al (2020) showed that exosomal miR-144 derived from MSCs targets the regulation of the PTEN/AKT pathway, thus improving the apoptosis of cardiomyocytes under hypoxia. Geng et al (2020) showed that miR-143, which is derived from serum exosomes, promotes myocardial angiogenesis through the IGF-IR/NO pathway.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…In rat myocardial infarction model, Wang et al showed that the cardioprotective effect of MSC exosomes was mediated by miR-21 enhanced cell survival via the PTEN/Akt pathway [93]. A recent study reported that MSC exosomes containing miR-25-3p had cardioprotective effects by decreasing EZH2, H2K27me3, and SOCS3 expression, alleviating myocardial infarction by targeting pro-apoptotic proteins and inflammatory genes [94]. According to the finding that MSCderived exosomes promote angiogenesis remodeling and functional recovery after stroke, a recent clinical study form Isfahan University of Medical Sciences is exploring the use of miR-124-loaded MSC-derived exosomes to improve angiogenesis in patients with acute stroke (NCT03384433).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Many studies have found that BMMSC-derived exosomes (BMMSC-Exos) can regulate the local inflammatory cytokines in infarcted myocardium. The injection of BMMSC-Exos could greatly repress inflammatory cytokines including IL1B, IL6 and TNFA which were induced by AMI, as well as targeting pro-apoptotic proteins like FASL and PTEN to alleviate MI mainly through miR-25 71 . Further studies confirmed that BMMSC-Exos could promote the polarization of M1 macrophages to the M2 macrophages both in vivo and in vitro , thereby alleviating inflammation response.…”
Section: Immune Cell-derived Exosomes In Immunomodulation After Amimentioning
confidence: 99%